Influence of soil applied zinc on productivity of soybean (Glycine max) in south-western Rajasthan - JAT, GAJANAND; SHARMA, SHANTI KUMAR; MEENA, R H; JAIN, DEVENDRA; CHOUDHARY, ROSHAN; CHOUDHARY, R S; YADAV, S K; SUMERIYA, H K; CHHIPA, B G (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted to study the influence of soil applied zinc on productivity, nutrient uptake and profitability of soybean (Glycine max L.) under Typic Haplustepts soil of sub-humid southern plain and aravalli hills region of Rajasthan during kharif 2016 and 2017. The treatments were consisted of five levels of zinc, viz. zero (control), 3 kg Zn/ha, 4 kg Zn/ha, 5 kg Zn/ha and 6 kg Zn/ha with four replications. Results revealed that significantly (P=0.05) maximum number of pods per plant, number of seeds per pod, test weight, seed yield, haulm yield, biological yield, nutrient content and uptake (N, K and Zn) in seed and haulm, net return and B:C ratio were recorded with the application of zinc @ 6 kg/ha along with the recommended dose of fertilizer (NPK) during 2016-17 and in pooled basis. However, the increase was significant up to 5 kg Zn/ha during both the years as well as in pooled analysis which was found statistically at par with 6 kg Zn/ha. Whereas, the application of zinc significantly decreased the phosphorus content in seed and haulm as compared to control and phosphorus uptake by seed and haulm was found to be non-significant with the application of zinc during both the years as well as in pooled analysis. The application of recommended dose of fertilizer along with combined application of Zn @ 5 kg/ha offered the best combination in realizing maximum yield of soybean and maximizing the economics both in absolute terms (net returns) and benefit-cost ratio.